STRUCTURAL FAILURES OF EARTH DAMS IN NIGERIA: A CASE STUDY OF CHAM DAM IN GOMBE STATE (2010)
The study investigates the reasons for failure of earth dams in Nigeria with emphasis on dams owned by the River Basin Development Authorities of the Federal Ministry of Agriculture and Water resources us; ng Ch m dam in Gombe State as case study. The general causes of earth dam failure were considered with emphasis on failures due to engineering factors. Cham dam failed in September 1998 after commissioning in December 1992 as a result of poor planning, inadequate study, inconsistent design, un-engineered construction and lack of dam safety monitoring team at site. Based on the findings, suggestions were given on how earth dam failures in Nigeria can be minimized in terms of adequate feasibility studies, good design, appropriate construction and an improved maintenance culture.